Bacterial foraging optimization algorithm used to adjust the parameters of Power System Stabilizers and Thyristor Controlled Series Capacitor-Power Oscillation Damping controller - De Menezes, Maxwell Martins; De Araujo, Percival Bueno [UNESP]; De Vargas Fortes, Elenilson (Institute of Electrical and Electronics Engineers (IEEE), 2014)
The objective of this paper was to use the Bacterial Foraging Optimization algorithm to determine the parameters of Power System Stabilizers and a Thyristor Controlled Series Capacitor-Power Oscillation Damping controller. The proposal is to synchronize adjustments of these controllers in order to introduce the desired low frequency oscillation damping in an electric power system. A test system distributed in two areas with 4 generators, 10 bus and 15 transmission lines and with local and inter-area oscillation modes is simulated to test the design. The results demonstrate the ability of the algorithm to achieve the objectives defined in this paper.
Keywords: Bacterial foraging optimization; POD; PSS; Small-signal stability; TCSC